Evaluation of Alcohol Taxes as a Public Health Opportunity to Reduce Liver Transplant Listings for Alcohol‐Related Liver Disease. (16th October 2020) - Shen, Nicole T.; Bray, Jeremy; Wahid, Nabeel A.; Raver, Michael; Hutchison, Nicholas; Brown, Robert S.; Schackman, Bruce R.
Abstract : Background: Alcohol‐related liver disease (ALD) is a leading indication for liver transplantation. Methods: State consumption of spirits, wine, and beer was determined from published sources. Excise and ad valorem alcohol taxes of spirits, wine, and beer were calculated following standard practices and correlated using multiple logistic regression models to 2002 to 2015 ALD transplant listing data from the United Network for Organ Sharing database. Results: 21.22% (29, 161/137, 440) of transplant listings were for ALD. Increased consumption of spirits was associated with increased ALD transplant listings (odds ratio [OR]: 1.67; 95% CI: 1.12 to 2.49, p = 0.01), but wine and beer consumption did not have a statistically significant association with ALD transplant listings. Spirits excise taxes on‐ and off‐premise were inversely associated with ALD transplant listing (OR: 0.79 and 0.82, respectively, both p < 0.02). Beer and wine taxes were not significantly associated with ALD transplant listings. Conclusions: Transplant listings for ALD are directly associated with spirit consumption and inversely associated with spirits excise taxes. These findings suggest a possible public health benefit of increasing excise taxes for spirits. Abstract : The burden of alcohol‐related liver disease (ALD) is increasing, and one possible strategy for mitigatibg this burden involves increasing alcohol taces. We found that spirits excise taxes were inversely associated with ALD transplant listing. Beer and wine taxes were not significantly associated with ALD transplant listings. These findings suggest a possible public health benefit of increasing excise taxes for spirits.